FORCE MAJEURE SEBAGAI ALASAN PEMBEBASAN TANGGUNG JAWAB DALAM HUKUM PERIKATAN - M. Rasya Anugrah Putra Rafa; Aldan Nugraha; Hagi Atful Ginani; Hilmanul Hamdi (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
An agreement creates legal rights and obligations that must be fulfilled by each party. However, in its implementation, there are circumstances beyond the control of the parties that prevent contractual obligations from being performed. Such circumstances are known as force majeure or overmacht. Indonesian Civil Code recognizes force majeure as a legal basis for exempting a debtor from liability for compensation, as stipulated in Articles 1244 and 1245 of the Civil Code. This study aims to analyze the concept of force majeure as a basis for releasing liability in the law of obligations, examine the legal elements of force majeure, and analyze its legal consequences for contractual relationships. This research employs a normative legal research method using statutory, conceptual, and case approaches. Primary legal materials consist of the Indonesian Civil Code and relevant legislation, while secondary legal materials include legal textbooks, scientific journals, and previous studies. The results indicate that force majeure can eliminate the debtor's obligation to compensate for losses if the inability to perform the obligation is caused by an unforeseeable event beyond the debtor's control and without any fault on the debtor's part. Nevertheless, the application of force majeure must be assessed carefully because not every obstacle in contract performance automatically qualifies as force majeure. Therefore, legal certainty regarding the interpretation and implementation of force majeure is essential to ensure justice and balance between creditors and debtors.